Coenurosis in sheep - Stigger, Adriana L.; Pavarini, Saulo P.; Guterra, Irene; Pereira, Francine F.; Paz, Milena Carolina; Silva, Emanoelly M. S. da; Barros, Claudio S. L.; Rissi, Daniel R. (Brazilian Journal of Veterinary Pathology, 2025)
Cases of neurologic disease occurred in a sheep farm in late 2023, with a surge in cases in July 2024. The disease affected lambs more frequently. Clinical signs lasted from 7 days to 1 month and included blindness, ataxia, lateral deviation of the head, circling, and reflux of ruminal contents through the nose. One animal had exophthalmos. There were several dogs on the farm. The total number of sheep on the farm was 100 and 50 were in the group where the disease occurred. Six of those 50 had clinical signs and died. All sheep were free in the pasture.